Intelligent medical data recording & management system - Foad, Motasim; Rafa, Israt Sahira; Navid, Sheikh Redwan Ahmed (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.